2022
DOI: 10.1093/plankt/fbac010
|View full text |Cite
|
Sign up to set email alerts
|

Plankton community response to fronts: winners and losers

Abstract: Fronts are particularly productive regions of the ocean, and biodiversity hotspots for many marine species. Here we use an ocean-ecosystem model to investigate the effect of fronts on plankton ecology. We focus on energetic fronts in Western Boundary Current systems that efficiently inject nutrients into the euphotic layer and which are physical boundaries between productive and oligotrophic provinces. We found that the fronts form an environment distinct from both provinces, favorable to some plankton groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…Peak diversity at the meander boundary could therefore be explained by the bell-shaped Productivity/Diversity Relationship (Kassen et al, 2000;Vallina et al, 2014), which suggests decreasing diversity in a region where nutrient concentrations are high enough for specific clades to dominate. This effect is also found in the DARWIN ocean-ecosystem model, with increased group and intra-group diversity in frontal regions (based on Shannon index), which was more pronounced for the lower nutrient subtropical front than the higher nutrient subpolar front (Mangolte et al, 2022). The frontal system of the STF meander investigated in this study could therefore contain a 'sweet spot' of nutrient concentrations for a balanced and diverse protist community (Figure 8).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Peak diversity at the meander boundary could therefore be explained by the bell-shaped Productivity/Diversity Relationship (Kassen et al, 2000;Vallina et al, 2014), which suggests decreasing diversity in a region where nutrient concentrations are high enough for specific clades to dominate. This effect is also found in the DARWIN ocean-ecosystem model, with increased group and intra-group diversity in frontal regions (based on Shannon index), which was more pronounced for the lower nutrient subtropical front than the higher nutrient subpolar front (Mangolte et al, 2022). The frontal system of the STF meander investigated in this study could therefore contain a 'sweet spot' of nutrient concentrations for a balanced and diverse protist community (Figure 8).…”
Section: Discussionsupporting
confidence: 72%
“…Heterotrophic taxa increased in abundance at the meander boundary, including the parasitic Syndiniales (Alveolata) as well as multiple Rhizarian groups (Acantharea, Polycystinea, and RAD‐C). Ocean‐Ecosystem modelling suggested that diatoms, dinoflagellates, and large carnivorous zooplankton benefit most from frontal environments, while coccolithophores and pico‐phytoplankton groups and small grazers also increase but are less favoured (Mangolte et al, 2022). The modelling study proposed that nutrient enrichment may enhance the prevalence of fast‐growing plankton groups.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of modeling work suggests that the ageostrophic secondary circulation at major oceanic fronts will lead to an enhancement of chlorophyll-a (chl-a) due to vertical transport of nutrients into the euphotic zone (Clayton et al, 2013;Lévy et al, 2015 and citations therein). Recent satellite observational work confirms this modeling result and suggests these mechanisms are at play (Haëck et al, 2023;Mangolte et al, 2022); however, satellite observations are restricted to the surface, at a resolution of ~1km and are limited in their ability to mechanistically link physical processes to phytoplankton dynamics. Previous submesoscale surveys observed increased biomass and diversity at WBC fronts, but they are typically limited in temporal scope to a single short period or feature (Clayton et al, 2017).…”
Section: Introductionmentioning
confidence: 57%
“…While SST satellites have sufficient spatial resolution, there is no temperature signature because this water mass would appear as a mixture of shelf and Gulf Stream water origins rather than deeper Gulf Stream or Sargasso Sea water. This conduit to the Gulf Stream and Sargasso Sea nutrient strata could enhance primary production at the front and could be a large component of increased productivity at the front seen in models and satellite data (Haëck et al, 2023;Mangolte et al, 2022). To constrain the total impact of these events, further work is needed to pinpoint the along-stream extent of this process, over what duration the high vertical velocities exist, and under what conditions it leads to growth enhancement.…”
Section: Obduction Of Sargasso Sea Watermentioning
confidence: 99%
“…Moreover, key organism traits, such as growth and prey ingestion rates, vary across functional groups (Ward et al, 2012; Kiørboe and Hirst, 2014). Therefore, it is critical for coupled plankton community and biogeochemical models to resolve multiple functional groups and organism sizes within groups (e.g., Dutkiewicz et al (2015b); Mangolte et al (2022); Dutkiewicz et al (2021)).…”
Section: Introductionmentioning
confidence: 99%